Social Capital - Sandra Landhäußer; Holger Ziegler (Social Work and Society)
In the broadest sense social capital reflects the idea of resources rooting in relations between individuals resp. in the embeddings of people in groups, associations, communities and even societies. A central assumption is that social capital - as a resource - is emerging from the quality of these relationships. This quality may be described in a more materialistic sense because these relations open up access to specific resources or assets. But it may also be imbued with valuated connotations, in particular referring to the essential contribution of networks and trust in promoting well-being, a sense of belonging and decency as individuals in entities blessed with social capital are pretended to engage in mutually beneficial collective actions. Therefore social capital applies to peoples' shared expectations, norms, values, and beliefs, their commitments to each other and eventually their associative capacities to knit the 'social fabric'.